Combination of techniques to control invasive grasses and restore Brazilian savannah : steps to achieve large-scale restoration - Coelho, Augusto Cesar Silva (2022)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Ciências Biológicas, Programa de Pós-Graduação em Ecologia, 2022.